Laparoscopic management of adnexal masses in admitted patients at tertiary care centre, Bhilai, Chhattisgarh, India - Naik, Meena; Singh, Pooja; Ratnani, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Laparoscopy is most widely accepted procedure in gynaecological cases both for diagnostic and operative purposes. It is associated with early recovery, shorter hospital stay and significant patient satisfaction. This study has been conducted to evaluate the effectiveness and safety of laparoscopy in the management of adnexal masses. Our Primary aim was to find out indications, intraoperative findings and different interventions to deal with adnexal mass. The objective of the study was to determine laparoscopic management of adnexal mass in all women attending Obstetrics and Gynaecology department, Shanakaracharya Institute of Medical Science, Bhilai, Chhattisgarh. Methods: This is a retrospective record-based observational study conducted over a period of one year from March 2020 to March 2021 after getting approval from the institutional ethical committee. Patients diagnosed with adnexal mass were evaluated and data was collected and analyzed. Results: Of the 130 cases of adnexal mass admitted in the hospital during the period under review, 43 cases (33%) were diagnosed as ovarian cyst among which simple cystic ovarian cyst was found to be most common etiology followed by ectopic pregnancy (41 cases). Majority of cases were managed laparoscopically with a good success rate, better outcome and short hospital stay. Conversion rate to laparotomy was 3.8% mainly seen in cases with complex ovarian mass or dense adhesions. Conclusions: Diagnosis of adnexal mass is important and it may affect females of any age group. Laparoscopy is a better approach to deal with adnexal masses (except malignancy) as it has better paronamic vision with less complications, less post-operative pain, shorter hospital stay. Careful patient selection should also be taken into account. Current study is an overview in favor of laparoscopic management of adnexal mass.